Utilizing wind rose information for the prediction of ammonia migration - Abdul Gafor, Abdani; Adam Assim, Mohd Ibrani Shahrimin; Marzuki, Omar Faruqi; Lahuri, Azizul Hakim; Adam, Nor Mariah (Human Resource Management Academic Research Society, 2023)
Exposure to high concentrations of ammonia can be harmful to human health. Ammonia is a strong irritant and can cause respiratory problems, such as coughing, wheezing, and shortness of breath. Prolonged exposure to high concentrations of ammonia can also cause damage to the lungs, and in severe cases, can lead to death. In addition to respiratory effects, ammonia exposure can also cause eye, nose and throat irritation, skin rashes and other symptoms. At high concentrations, ammonia can also cause chemical burns to the skin and eyes. The severity of the health effects will depend on the concentration of ammonia, the duration of exposure, and the specific characteristics of the individual exposed, such as their age, health, and any pre-existing respiratory condition. Wind can affect the migration of ammonia by influencing the dispersion and diffusion of the gas. Strong winds can disperse ammonia over a wide area, reducing the concentration in any one location. Conversely, calm winds can cause ammonia to accumulate in a specific area, leading to higher concentrations. The direction and strength of the wind can also affect the direction of ammonia migration, potentially carrying the gas towards or away from sensitive areas such as residential neighbourhoods or wildlife habitats. A wind rose is a graphical representation of the distribution of wind speeds and directions at a specific location. It is often used to understand the dominant wind patterns and how they may influence the dispersion of pollutants such as ammonia. The direction from which the wind is blowing is represented on the outer circle, with the wind speed represented on the inner circles. When it comes to ammonia dispersion, the wind rose can be used to understand how the dominant wind patterns in a specific location may influence the spread of ammonia emissions. For example, if the wind rose shows that the dominant winds are blowing from the direction of an ammonia source, such as a fertilizer plant, towards a sensitive receptor, such as a residential area, it can be an indication that the ammonia emissions from the source may pose a higher risk to the residents living in the area. Additionally, the wind rose can also be used to understand how the wind patterns may influence the dispersion of ammonia emissions within the atmosphere. If the wind rose shows that the dominant winds are blowing in a specific direction, it can indicate how the ammonia emissions will be transported and dispersed in the atmosphere. In summary, the wind rose is an important tool for understanding the wind patterns in a specific location and how they may influence the dispersion of ammonia emissions. It can be used to assess the potential risks associated with ammonia emissions and to make recommendations for controlling or mitigating ammonia migration strategies.